Translanguaging and Reading Comprehension of Filipino ESL Intermediate Learners - Ocampo, Darrel (Journal of Natural Language and Linguistics, 2023)
This study investigated the connection between translanguaging and reading comprehension of Filipino ESL intermediate learners. The respondents were intermediate pupils enrolled in the selected central schools in Bicol, Philippines. The respondents’ ages range from 8 to 12 years old, and 124 students (27.55%) were males while 326 students (72.44%) were females. The descriptive-correlational method was used in the study. The descriptive method was used to describe the reading performance of the ESL intermediate learners and their translanguaging factors, while Pearson Product Moment Correlation was used to determine the relationship between the two variables. The primary instruments used were validated teacher-made reading comprehension test and translanguage factors survey questionnaire. Data disclosed that the general reading comprehension of the ESL intermediate learners along with vocabulary, drawing inferences, and getting the main idea, are very satisfactory. Meanwhile, the different translanguaging factors, along with personal, teacher, and social, were surveyed and identified in the study. The statistical test revealed that the reading comprehension of the respondents was significantly correlated with the identified translanguaging factors. Thus, it is recommended that teachers should promote group discussions and allow open interactions in the classroom. Teachers should allow the use of both the home language and English; employ translanguaging pedagogy in teaching reading; foster an understanding and acceptance of linguistic differences; promote multilingualism, and allow indigenous languages to be used in education to facilitate meaningful learning.